Temperature-Mediated Competition Between the Invasive Larger Grain Borer (Coleoptera: Bostrichidae) and the Cosmopolitan Maize Weevil (Coleoptera: Curculionidae). Issue 1 (18th December 2019) - Quellhorst, Hannah; Athanassiou, Christos G; Bruce, Alexander; Scully, Erin D; Morrison, William R
Abstract: Interspecific competition between agricultural pests may affect the species that can establish, and may also affect food production. Prostephanus truncatus (Horn), the larger grain borer, is endemic to Central America, but invaded Africa with disastrous consequences for maize production. Its main competitor is Sitophilus zeamais Motschulsky, the maize weevil, which is cosmopolitan. These insects co-occur in many regions of the world and both are threats to maize. However, the impact of competition between these two species is not well-understood, nor is its effect on grain quality or potential to limit P. truncatus invasion in new areas. The aims of our study were to evaluate the outcome of interspecific competition between P. truncatus and S. zeamais at four different temperatures on a fixed quantity of grain, and determine effects on progeny production, grain damage, and mold growth. We found that coexistence may be possible at a range of 25–30°C, but mixed colonies experienced a direct competitive cost compared to single-species colonies. Prostephanus truncatus performed better at warmer temperatures, while S. zeamais favored cooler temperatures. The majority of grain damage was the result of P. truncatus activity as opposed to S. zeamais . Finally, mold growth was greater where both species were present, and species of mold that produce aflatoxin were identified. Although there are an increasing number of areas where both of these species occur, our results suggest P. truncatus will be capable of destroying much more maize in a shorter period compared to S. zeamais at temperatures greater than 25°C.